Efforts of Islamic Religious Education Teachers in Implementing Multicultural Education to Grade IX Students at SMP Negeri 11 Baubau - Inang, Inang; Madi, Madi; Basri, Basri (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to outline and evaluate the efforts made by Islamic Religious Education (IRE) instructors at SMP Negeri 11 Baubau to introduce intercultural education to eleventh-grade students. The background of this research is based on the importance of multicultural education in shaping attitudes of tolerance, respect for diversity, and fostering a harmonious school environment amid students' diverse cultural, religious, and social backgrounds. This study uses a case study methodology in conjunction with a qualitative approach. Techniques for gathering data include documentation, in-depth interviews, and observation. The findings show that through instructional resources, interactive teaching techniques, and setting an example of behavior, IRE teachers actively contribute to the integration of multicultural values into the learning process. Additionally, educators support the growth of a diverse and inclusive school culture. Despite obstacles including pupils' poor comprehension of diversity and classroom time limits, overall efforts have improved students' character development by encouraging tolerance, openness, and respect for one another. As a result, Islamic Religious Education's multicultural curriculum strategically contributes to fostering social harmony in the classroom.